Distribution of Central Line-Associated Bloodstream Infections Determined From Washington State's Annual Reporting Validation Program, 2009–2013. (28th December 2016) - Lempp, Jason M.; Cummings, M. Jeanne; Birnbaum, David W.
Abstract : Healthcare-associated infection reporting validation is essential because this information is increasingly used in public healthcare quality assurances and care reimbursement. Washington State's validation of central line-associated bloodstream infection reporting applies credible quality sciences methods to ensure that hospital reporting accuracy is maintained. This paper details findings and costs from our experience. Infect Control Hosp Epidemiol 2017;38:489–492